Pendampingan Pembuatan dan Publikasi Karya Ilmiah Penelitian Tindakan Kelas untuk Kenaikan Pangkat Guru - Adi Candra Kusuma; Hari Tri Wibowo; Gillang Al Azhar; Almas Adibah; Odhitya Desta Triswidrananta; Wahyu Tri Wahono; Sidik Nurcahyo (TAAWUN, 2024)
Community Service Activities (PPM) aim to help teachers develop ideas in the form of written scientific papers which are then published in the form of textbooks or scientific articles. This Requirements activity can also be used as a supporting point in teacher promotion. The method of implementing activities begins with a) data collection, b) preparation of plans, c) implementation of activities, d) evaluation of activities, and e) publication. The method of implementing activities is by assisting in transmission. The results of PPM activities include: (1) participants get an introduction to PTK with various learning methods, (2) participants receive assistance in making PTK, and (3) participants receive assistance in drafting journal articles/proceedings using the journal template they are going to. This service activity received a positive response as shown by looking at the results of the questionnaire as much as 87% of the activity can motivate and increase knowledge before receiving assistance by 72% regarding PTK as well as preparing draft publications through textbooks and scientific articles.